Pengaruh Penambahan Ekstrak Bawang Tiwai (Eleutherine americana Merr) pada Komposisi Kimia, Kualitas Fisik, Organoleptik dan Vitamin C Nugget Ayam Arab (Gallus turcicus) - A Ismanto; D Arsanto; Suhardi Suhardi (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2014)
This research was conducted to know the effect of different concentrations addition of Tiwai onion extract (Eleutherine americana Merr) on chemical composition, physical, organoleptical quality, and Vitamin C content of nugget from Gallus turcicus meat. There were four treatments in this experiment, 1) without Tiwai onion extract (TOE), 2) level of 5 % TOE, 3) level of 10 % TOE, 4) level of 15 % TOE. The variable were observed of chemical composition (water, fat, and ash content), physical quality (pH and cooking loss) and sensoric quality (colour, taste, tenderness, texture and acceptability). Chemical composition and physical quality were analysed by ANOVA, when the different between means were tested by Least Significant Difference Test. Sensory characterictic quality were analysed by hedonic test of Kruskal and Wallis. Result showed that the addition of TOE up to 15 % affected significantly on water, fat, ash and vitamin C content (P<0.05). Addition of TOE was also affected significantly (P<0.05) onpH, cooking loss and all organoleptical quality except acceptability. Result showed that the addition of TOE up to 15 % increasing water, fat, ash and vitamin C content. Addition of TOE up to 15% decreasing physical quality (pH and cooking loss). Organoleptical quality taste, flavor, texture and tenderness increased but colour was decrease compare to control. Nugget by addition EBT up to 15 % still acceptable for panelis.Key words: nugget, Eleutherine americana Merr extract, chemical composition, physical quality, organoleptical quality, vitamin C content